PHARMACOECONOMIC ANALYSIS OF BRENTUXIMAB VEDOTIN THERAPY IN RELAPSED OR REFRACTORY CD30+ SYSTEMIC ANAPLASTIC LARGE CELL LYMPHOMA IN PATIENTS OVER 18 YEARS OF AGE: HEALTH BUDGET IMPACT ANALYSIS - A. S. Kolbin; I. A. Vilum; М. A. Proskurin; Yu. E. Balykina (Фармакоэкономика, 2017)
Objectives. To provide a pharmacoeconomic analysis of brentuximab vetodin therapy in relapsed or refractory CD30+ systemic anaplastic large-cell lymphoma in patients over 18 years of age.Methods. Recommendations to carry out a budget impact analysis in theRussian Federation (2016) were used.Results. The analysis covered a period of 3 years. The target population of patients with relapsed or refractory CD30+ systemic anaplastic large cell lymphoma numbered 345 individuals. The results indicate that the introduction of brentuximab vetodin in the List of vital and essential drugs and the Program of state-guaranteed free medical care will not increase the costs of the treatment in patients with relapsed or refractory CD30+ systemic anaplastic large cell lymphoma.Conclusion. The brentuximab vetodin therapy of relapsed or refractory CD30+ systemic anaplastic large cell lymphoma is an economically reasonable and resource-saving medical modality.